Improving Understanding of Islamic Banking Materials through Interactive Learning Based on Quartet Cards and Concept Maps among Grade X Students - Novita Lailatul Maghfiroh; Tamani Tamani (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2026)
This classroom action research aimed to improve students' understanding of Islamic banking materials through interactive learning in Grade X at MAN 1 Gresik. The study involved 34 students in the even semester of the 2025/2026 academic year and followed the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection in two cycles. The interactive learning action was implemented through quartet-card learning activities in Cycle I and concept-map construction in Cycle II as an improvement based on reflection. Data were collected through pretest and posttest activities, student-activity observation sheets, student-response questionnaires, and documentation. The data were analyzed descriptively using mean scores, the number of students who met the minimum mastery criterion (75), and the percentage of learning mastery. The results showed an increase in students' understanding from a pretest mean score of 54.2 with 11.8% mastery (4 of 34 students), to 72.4 with 61.8% mastery in Cycle I (21 students), and to 86.1 with 91.2% mastery in Cycle II (31 students). These findings indicate that the interactive learning action achieved the success indicator and supported improved participation, motivation, and conceptual understanding of Islamic banking.